2015
DOI: 10.1242/jeb.111013
|View full text |Cite
|
Sign up to set email alerts
|

Erection pattern and section-wise wettability of honeybee glossal hairs in nectar feeding

Abstract: The honeybee's tongue (glossa) is covered with bushy hairs and resembles a mop or a brush. We examined the dimensions of glossal hairs of the Italian honeybee (Apis mellifera ligustica) and found that the average length of hairs increased from the proximal segment to the distal end. The glossal dynamic surface of a honeybee in drinking cycles was captured by a specially designed high-speed camera system, and we discovered that the glossal hairs erected rhythmically when drinking nectar; specifically, hairs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…The labium constitutes the bottom, the stipites including the laciniae and galeae form the sides and the labrum/epipharynx composes the roof of this short temporary food tube (Duncan 1939) which was termed "Wespenrüssel" (Kirmayer 1909) or "wasp proboscis". The glossae and paraglossae produce lapping motions, similar to the "licking cycle" in honey bees (Snodgrass 1956, Wu et al 2015. In the extended position of the ligula, liquid adheres to the spatula-shaped microtrichia that is thus transported into the food canal when the glossae and paraglossae are retracted towards the mouth (Seifert 1995).…”
Section: Fluid Feeding In Waspsmentioning
confidence: 99%
“…The labium constitutes the bottom, the stipites including the laciniae and galeae form the sides and the labrum/epipharynx composes the roof of this short temporary food tube (Duncan 1939) which was termed "Wespenrüssel" (Kirmayer 1909) or "wasp proboscis". The glossae and paraglossae produce lapping motions, similar to the "licking cycle" in honey bees (Snodgrass 1956, Wu et al 2015. In the extended position of the ligula, liquid adheres to the spatula-shaped microtrichia that is thus transported into the food canal when the glossae and paraglossae are retracted towards the mouth (Seifert 1995).…”
Section: Fluid Feeding In Waspsmentioning
confidence: 99%
“…In addition, a similar feeding mechanism might take place in other, more distantly related insect groups. The mouthparts of the nectar-feeding cricket Glomeremus orchidophilus Hugel et al (Gryllacrididae) [38] and the honeybee Apis mellifera L. (Apidae), for instance, might also involve the employment of capillary action [39][40][41], and exhibit a relationship between the sizes of spaces between their mouthpart structures and the sizes of substrate pores from which they can feed.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of glossal hairs of the Italian honeybee (Apis mellifera ligustica) were examined by (Amirouche et al, 2009) and they found that the average length of hairs increased from the proximal segment to the distal end. Wu et al (2015) discovered the function of the glossal hair and reported that when drinking nectar, the glossal hairs erected rhythmically; specifically, hairs on the proximal segment erected before those on the distal end of a honeybee's tongue, and this was described as asynchronous hair erection. Moreover, they found that the flabellum was the most hydrophilic and the root of the tongue was hardest to be wetted by measuring the wettability of the tongue.…”
Section: Importance Of Morphological Measurementsmentioning
confidence: 99%
“…The nectar drinking strategy has been studied extensively and the erection of glossal hairs has been revealed in several researches (Cook, 1880;Snodgrass, 1956;Dade, 2009). The rhythmical erection pattern of honeybees' glossal hairs in nectarfeeding has been reported, but the role of the deformable tongue structure in nectar-feeding has not been investigated yet (Wu et al, 2015). In this work, we focused on the deformation of the proboscis formation of honeybees, especially the morphing of the hair pattern, and its supposed influence on the feeding type and efficiency.…”
Section: Introductionmentioning
confidence: 99%